Rachunkowość jako system wspomagający proces zarządzania jednostkami gospodarczymi - Toborek-Mazur, Joanna (Accounting as a System Aiding the Process of Managing Economic Units, 2007)
The target of this article is to present accounting as a tool of managing system. Through its functions accounting delivers information which is essential for decision making by managers. Generated information in this system lets evaluate activities of companies and effective usage of its resources and taking good decisions in managing process. The main focuses of management are efficiency and effectivity of organisation and the maximization of profit in economic area. It cannot be reached without information given and processed by accounting. The right strategy of managing based on the credible and reliable information is a tool which will contribute to the success of an organisation.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1174, s. 500-506